The potential of siRNA based drug delivery in respiratory disorders: Recent advances and progress. Issue 6 (16th July 2019) - Dua, Kamal; Wadhwa, Ridhima; Singhvi, Gautam; Rapalli, Vamshikrishna; Shukla, Shakti Dhar; Shastri, Madhur D.; Gupta, Gaurav; Satija, Saurabh; Mehta, Meenu; Khurana, Navneet; Awasthi, Rajendra; Maurya, Pawan Kumar; et al.
Abstract: Lung diseases are the leading cause of mortality worldwide. The currently available therapies are not sufficient, leading to the urgent need for new therapies with sustained anti‐inflammatory effects. Small/short or silencing interfering RNA (siRNA) has potential therapeutic implications through post‐transcriptional downregulation of the target gene expression. siRNA is essential in gene regulation, so is more favorable over other gene therapies due to its small size, high specificity, potency, and no or low immune response. In chronic respiratory diseases, local and targeted delivery of siRNA is achieved via inhalation. The effectual delivery can be attained by the generation of aerosols via inhalers and nebulizers, which overcomes anatomical barriers, alveolar macrophage clearance and mucociliary clearance. In this review, we discuss the different siRNA nanocarrier systems for chronic respiratory diseases, for safe and effective delivery. siRNA mediated pro‐inflammatory gene or miRNA targeting approach can be a useful approach in combating chronic respiratory inflammatory conditions and thus providing sustained drug delivery, reduced therapeutic dose, and improved patient compliance. This review will be of high relevance to the formulation, biological and translational scientists working in the area of respiratory diseases.